Ethical Considerations for Youth Treatment by the Media - Suárez Villegas, Juan Carlos (2011)
This article reflects on the Youth as a stage of transition and change in human life that has been interpreted, in many ways, by the Media. Young people often represent an icon of the breakdown of social order, which incurred easy to speculate on authorship in any act of criminality. On the other hand, reflects a confused image of proportion to its reality and its efforts to train and integrate into the labor market. Instead, they are used as symbols of the promise of future political messages. This ambiguity can lead to a stereotype of youth condition their perception of the elderly. This article suggests ways to improve theimage of young people in the Media.